Strange bodies on a stranger shore - Copeland, Ann. (Toronto : CNIB, 2005)
Claire Delaney left her convent after eleven years as a nun. Now married with grown children, she explores the complicated territory of middle age. Some of the stories depict actual or emotional pilgrimages to the past, as when Claire honours an unexpected summons from her former Mother Superior, now dying and wishing to see her. In the final story, she agrees to go on a television talk show to explain why she became a nun and why she abandoned that life. Sequel to "The golden thread". 1994.
Search and access by headings.
Aileen Seaton.
Audio and text.
System requirements: IBM PC or compatible; double speed or faster CD-ROM drive; sound card and sound output device; DAISY playback software or DAISY talking book player.
Recording standard: DAISY 2.02 standard.
MP3 compression.